Rotational Spectroscopy Meets Quantum Chemistry for Analyzing Substituent Effects on Non-Covalent Interactions: The Case of the Trifluoroacetophenone-Water Complex - Juncheng Lei; Silvia Alessandrini; Junhua Chen; Yang Zheng; Lorenzo Spada; Qian Gou; Cristina Puzzarini; Vincenzo Barone (Molecules, 2020)
The most stable isomer of the 1:1 complex formed by 2,2,2-trifluoroacetophenone and water has been characterized by combining rotational spectroscopy in supersonic expansion and state-of-the-art quantum-chemical computations. In the observed isomer, water plays the double role of proton donor and acceptor, thus forming a seven-membered ring with 2,2,2-trifluoroacetophenone. Accurate intermolecular parameters featuring one classical O-H···O hydrogen bond and one weak C-H···O hydrogen bond have been determined by means of a semi-experimental approach for equilibrium structure. Furthermore, insights on the nature of the established non-covalent interactions have been unveiled by means of different bond analyses. The comparison with the analogous complex formed by acetophenone with water points out the remarkable role played by fluorine atoms in tuning non-covalent interactions.